2017
DOI: 10.1007/s00436-017-5693-6
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of aspirin treatment on mouse behavior in the acute phase of experimental infection with Trypanosoma cruzi

Abstract: Chagas disease is a potentially fatal disease caused by the parasite Trypanosoma cruzi, which can in some cases affect the central nervous system. The objective was to evaluate the effect of aspirin (ASA) in the behavior of mice infected with T. cruzi during the acute phase. This was an experimental study with random assignation. Twenty four BALB/c mice were divided into four groups of six animals each as follows: only ASA (OA), ASA before infection (BI), ASA after infection (AI) and only infection (OI). The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…The effect of ASA in reducing the parasitemia in the acute phase is quite well studied, but the findings are contradictory [ 112 , 113 , 114 , 115 ]. In a murine model of chronic Chagas disease, ASA decreased the amount of cardiac inflammatory infiltrates, showing a vascular-protective role in the endothelium [ 116 ].…”
Section: Resultsmentioning
confidence: 99%
“…The effect of ASA in reducing the parasitemia in the acute phase is quite well studied, but the findings are contradictory [ 112 , 113 , 114 , 115 ]. In a murine model of chronic Chagas disease, ASA decreased the amount of cardiac inflammatory infiltrates, showing a vascular-protective role in the endothelium [ 116 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, studies have shown that the administration of ASA prior to infection appeared to prevent the behavioural changes induced by acute infection, but led to accelerated mortality (Silvero-Isidre et al ., 2018). Molina-Berríos et al .…”
Section: Discussionmentioning
confidence: 99%